Climate change and income inequalities - Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
The relationship between climate warming and associated socio-economic development is a central question for environmental economists and social scientists. The scientific literature focusing on the economic effects of climate change is mainly based on the cross-sectional impact of temperature and precipitation on GDP growth. However, little is known about the effects of climate variations on income inequality. This paper aims at filling this gap by exploring the relationship between climate and income inequality. We use two different country-level panel datasets on income inequality: i) the Standardized World Income Inequality Database (Solt, 2016), which provides the GINI index, and ii) the World Income Inequality Database (Wider, 2008), which provides the share of income held by different classes of the population. We then match the two-income inequality indices with annual climate data for 165 countries from 1960 to 2010. Our analysis suggests a significant Ո-shaped relationship between inequality indices and annual mean temperature.
Keywords: 330; Income Inequality; climate change; GINI index; income distribution